NEW READING OF THE NOVEL 77 SUICIDES BY BRANKO VE POLJANSKI (Philological Studies, 2019)
The paper deals with the text 77 suicides by Branko Ve Poljanski (1923) as a construct that synthesizes genres: novels, poems, manifestos and advertisements and thus achieves an avant-garde concept of mounted artwork. It analyzes the possibility of establishing the composition of the novel on the experience of German Expressionist films, as well as the integration of expressive potential of differentiated art: literature, graphics, film and photography. The paper establishes a dialog relationship with theses by Richard Johnson (What is Cultural Studies Anyway?), with special emphasis on the concept of one of the dominant models of research in cultural studies - studies based on the text, which examines the possibilities for transformative cultural practices.
Keywords: Branko Ve Poljanski, avant-garde, cultural studies